Bactericidal antibiotic treatment induces damaging inflammation via TLR9 sensing of bacterial DNA - Julia L. Gross; Rahul Basu; Clinton J. Bradfield; Jing Sun; Sinu P. John; Sanchita Das; John P. Dekker; David S. Weiss; Iain D. C. Fraser (Nature Communications)
Abstract The immunologic consequences of using bactericidal versus bacteriostatic antibiotic treatments are unclear. We observed a bacteriostatic (growth halting) treatment was more protective than a bactericidal (bacteria killing) treatment in a murine peritonitis model. To understand this unexpected difference, we compared macrophage responses to bactericidal treated bacteria or bacteriostatic treated bacteria. We found that Gram-negative bacteria treated with bactericidal drugs induced more proinflammatory cytokines than those treated with bacteriostatic agents. Bacterial DNA – released only by bactericidal treatments – exacerbated inflammatory signaling through TLR9. Without TLR9 signaling, the in vivo efficacy of bactericidal drug treatment was rescued. This demonstrates that antibiotics can act in important ways distinct from bacterial inhibition: like causing treatment failure by releasing DNA that induces excessive inflammation. These data establish a novel link between how an antibiotic affects bacterial physiology and subsequent immune system engagement, which may be relevant for optimizing treatments to simultaneously clear bacteria and modulate inflammation.